Using population dynamics modelling to evaluate potential success of restoration: a case study of a Hawaiian vine in a changing climate – CORRIGENDUM. (28th August 2014) - WONG, TAMARA M.; TICKTIN, TAMARA
Abstract : In the article above two references were incomplete and the Acknowledgements section was missing.